**Weegy:** 6 + 3 x 42 – 7
a. 3 x 42 first = 126, so it would now be 6 + 1266 -7
b. 6 + 126 = 132, so it would now be 132 - 7
c. finally, 132 - 7 = 125

**User:** Simplify the following expression using PEMDAS 3 + 4[(8 ÷ 2) + 3]PLEASE SHOW THE DIFFERENTS STEPT

**Weegy:** 3 + 4[(8 ÷ 2) + 3]
a. (8 ÷ 2) = 4
b. [4 + 3] = 7
c. 3 + 4 + 7 = 14

**User:** Simplify the following expression using PEMDAS (6÷ 3) + 4(6÷2)2 PLEASE SHOW THE DIFFERENTS STEPT

**Weegy:**
(6÷ 3) + 4(6÷2)2
a. (6÷ 3) = 2 amd (6÷2) = 3, so now it would be 2 + 4 x 3 x 2
b. 4 x 3 = 12
c. 12 x 2 = 24
d. 2 + 24 = 26

(More)